Effect of Mental Health Programmes on the Attitudes and Awareness of Mental Illness among Students and Teachers of Secondary Schools in Benue State - Simon Terver Chieshe; Abraham Tersugh Kwaghgbah (ESUT JOURNAL OF SOCIAL SCIENCES, 2022)
This study investigated the effect of mental health programme on attitude and awareness of mental illness among students and teachers of secondary schools in Benue State. The study employed Between Subject Factorial design using 180 participants comprising of 60 teachers and 120 students. The study employed the use of stratified random sampling to draw the participants for the study. The instruments used for the intervention in this study were the Attitude towards Mental Illness Scale and the Mental Health Knowledge Schedule. Independent measures One-Way ANOVA was used to test the four hypotheses raised in the study. First, the result shows that there was a significant effect of mental health programme on the attitudes of teachers towards mental illness. Secondly, the result shows that there was a significant effect of mental health programme on the attitudes of students towards mental illness. Thirdly, the result shows that there was a significant effect of mental health programme on the knowledge of teachers concerning mental illness. Fourthly, the result also shows that there was a significant effect of mental health programme on the knowledge of students concerning mental illness. The study thus recommended that, there is urgent need to minimize the level of stigma and discrimination against people with mental illness.